Potentially serious alcohol–medication interactions and falls in community-dwelling older adults: a prospective cohort study. (3rd October 2019) - Holton, Alice; Boland, Fiona; Gallagher, Paul; Fahey, Tom; Moriarty, Frank; Kenny, Rose Anne; Cousins, Gráinne
Abstract: Objective: To investigate the association between potentially serious alcohol–medication interactions (POSAMINO criteria), hypothesised to increase the risk of falls in older adults, and falls in community-dwelling older adults at two and 4 years follow-up. Design: A prospective cohort study. Setting: The Irish Longitudinal Study on Ageing. Subjects: A total of 1, 457 community-dwelling older adults aged ≥65 years, with a complete alcohol and regular medication data to allow for the application of the POSAMINO criteria. Outcomes: Self-reported falls at 2 and 4 years follow-up, any falls (yes/no), injurious falls (yes/no) and number of falls (count variable). Results: The number of participants who reported falling since their baseline interview at 2 and 4 years were 357 (24%) and 608 (41.8%), respectively; 145 (10%) reported an injurious fall at 2 years and 268 (18%) at 4 years. Median (IQR) number of falls was 1 (1–2) at 2 years and 2 (1–3) at 4 years. Exposure to CNS POSAMINO criteria, hypothesised to increase the risk of falls due primarily to increased sedation, was associated with a significantly increased risk for falling (adjusted relative risk (RR) 1.50, 95% confidence interval (CI) 1.21–1.88) and for injurious falls (adjusted RR 1.62, 95% CI: 1.03–2.55) at 4 years. These equate to an absolute risk of 19% for falling (95% CI: 5–33%) and 8% for injurious falls (95% CI, 4–20%) at 4 years. Conclusions: Assessment and management strategies to prevent falls in community-dwelling older adults should consider patients' alcohol consumption alongside their assessment of patient medications, particularly among those receiving CNS agents.